JOE BIDEN AND EXTRAORDINARY MEASURES ON THE COVID-19 PANDEMIC - Mahendra, Igo Ilham; Loy, Nikolaus (Jurusan Ilmu Hubungan Internasional, 2025)
The phenomenon of the COVID-19 pandemic in the United States has sparked serious attention from Joe Biden. After constructing the security threat of the COVID-19 pandemic through a series of speeches and receiving a response from the audience. President Joe Biden then passed extraordinary measures to handle the COVID-19 pandemic in the United States. Joe Biden places high priority on the issue of the COVID-19 pandemic in the United States. This research aims to analyze the extent of Joe Biden's policies in responding to the COVID-19 pandemic problem in the United States. This research collects Joe Biden's policy texts regarding the COVID-19 pandemic problem in the United States right after assuming the 46th US presidency. The research method used is a qualitative and descriptive approach. The framework for this research uses securitization theory from the Copenhagen School of Security Studies (CSS). The results of this research show that in responding to the COVID-19 pandemic, Joe Biden drastically took action quickly, and urgently, also violated normal political rules in the form of the National Strategy for the COVID-19 Response and Pandemic Preparedness, and Executive Orders.